Kemampuan Membaca Pemahaman Mahasiswa di Lamongan - Kholiq, Abdul (Belajar Bahasa, 2020)
This study aims to analyze the reading comprehension ability of college students in the Lamongan Regency. The focus research is the level of literal, inferential, critical, and creative comprehension of college students in the Lamongan Regency. This research uses descriptive quantitative. The sample of this study was 373 Universitas Islam Lamongan students; 353 students of Universitas Islam Darul ‘Ulum Lamongan; 222 Universitas Billfath Lamongan. Data collection used a test. Data analysis is to find the mean value. The results of the study showed that the level of literal comprehension was 64.12 with a high category. The level of inferential comprehension was 57.95 in the medium category. The level of critical comprehension was 61.49 with a high category. The level of creative comprehension was 44.25 with a medium category. Of the four results above, the level of reading comprehension of college students in the Lamongan Regency is at a medium level with a mean 56.95. The results are above the average national literacy rate of 37.32.